Literature Review: The Role of Psychological Capital among Indonesianâs Worker - Prihatsanti, Unika (Journal of Educational, Health and Community Psychology, 2017)
AbstractPsychological capital is a positive psychological state, characterized by having self-efficacy, hope, optimism, and resiliency. The findings show that psycap plays a vital role in the emergence of positive behaviors at the workplace. This study aims to conduct a literature review on the role of psychological capital in workers from various settings in Indonesia. The literature search is done through portalgaruda.org and onesearch.id database using the keywords "psychological capital,", "psycap," and "modal psikologis," resulting in a total of 32 papers (N=2569). We found that there are various effects of individual psycap on employment behavior, and that no studies have been found on psycap measurements or interventions. Hence, the latter could be used as the direction for future research. This study answers the question of psycap consequences for Indonesian workers and, calls future researcher to expand on psycap antecedent and consequences. Keywords: employee, psychological capital, and worker.